Anticorpos anti-nucleossoma em pacientes com lupus eritematoso sistêmico: estudo longitudinal - Gutiérrez Adrianzén, Oswaldo Augusto (2002)
INTRODUCTION: Systemic Lupus Erythematosus (SLE) is a disease of autoimmune nature, characterised by the formation of immune complexes. Although preliminary studies pointed out to the double-stranded DNA (dsDNA) as the most important antigen in the pathogenesis of SLE, most recent studies have demonstrated the central role of the nucleossome as the major antigen of the repertoire of nuclear antigens, with the anti-nucleossome antibody preceding the appearance of anti-dsDNA and anti-histone antibodies. OBJECTIVES: To determine the prevalence of anti-nucleossome antibodies in SLE; to evaluate prospectively their diagnostic value in the general activity of the disease and in lupus nephritis; to compare prevalence, sensitivity, specifícity, positive and negative predictive values of anti-nucleossome, anti-dsDNA and anti-histone antibodies. PATIENTS AND METHODS: Patients with SLE diagnosis according to the American College of Rheumatology criteria, treated at Walter Cantídio University Hospital, Faculty of Medicine, Federal University of Ceará, Brazil, were sequentially evaluated for 12 months. In each evaluation, blood and urine samples were drawn for determination of whole blood count, urea, creatinine, albumin, C3, C4, ANA, anti-Sm, anti-Ro, anti-La, anti-RNP, urinalysis, and proteinuria of 24 hours. Anti-nucleossome, anti-dsDNA and anti-histone antibodies titers were determined at the Institut National de la Santé et de la Recherche Médicale (INSERM), Necker Hospital, Paris, France, through an Enzyme-linked immuno absorbent assay metliod (ELISA). The activity of the disease was scored in each evaluation according to LAAC and SLEDAI criteria. RESULTS: 113 patients were initially evaluated, but only 87 of them fulfilled tlie criteria of at least 8 evaluations during the 12-month period of follow-up, being thus the group considered for the prospective study. The most common clinicai manifestations present when patients first seen were: arthritis (69.0%) photosensivity (63.2%), skin lesions (59.8%) and nephritis (54.0%). 84 patients were female and 3 male, with an average age = 33.15 (SD = 10.90) years and average length of the disease = 60.70 (SD = 66.19%) months. The prevalence of nephritis varied ffoin 37 to 55.2%, with a trend to reduction from the second evaluation. Disease activity decreased during the follow-up, as it was noticed in 50.6% of the patients in the first evaluation and in only 29.1% of them at the end of the observation period. The prevalence of anti-nucleossome, anti-dsDNA and anti-histone antibodies in the general activity of the SLE varied in the twelve evaluations ffoin 66.7 to 83.7%, lfom 88.7 to 100% and from 84.3 to 98%, respectively. Sensitivity of anti-nucleossome, anti-dsDNA and anti-histone antibodies varied from 72.7 to 100%, from 31.3 to 54.8% and from 12.5 to 41.7%, respectively. Specificity of anti-nucleossome and anti-dsDNA antibodies in active lupus nephritis varied from 46.2 to 67.3% and from 85.1 to 97.5%, respectively. Sensitivity of these antibodies varied from 32.0 to 67.5% and from 16 to 35.4%, respectively. The positive predictive values of anti-nucleossome antibodies for the diagnosis of SLE activity in the next following month showed an acceptable variation (56.7% to 71.8%) from the first to the seventh evaluation, declining until 22.7% in the last five evaluations as the disease went under control in most patients. CONCLUSIONS: The present study shows a larger sensitivity of anti-nucleossome antibody titers as compared to anti-dsDNA antibodies in the assessment of the general activity of the disease and of lupus nephritis. On the other hand, although it appears to be less specific in comparison to anti-dsDNA leveis, specificity values of anti-nucleossome antibody titers obtained during the follow-up allow us to conclude tliat anti-nucleossome antibody titers can be considered as an extremely efficient serological marker of SLE, because it proved characteristics of excellent sensitivity and good specificity.